2020
DOI: 10.1155/2020/8752606
|View full text |Cite
|
Sign up to set email alerts
|

Activity Concentrations of Sr-90 and Cs-137 in Seawater and Sediment in the Gulf of Tonkin, Vietnam

Abstract: In this study, we measured the activity concentrations of Cs-137 and Sr-90 in surface seawater and surface sediments at the Tra Co, Bach Long Vi, and Ky Anh locations in the Gulf of Tonkin, Vietnam, from December 2018 to October 2019. The average activity at the selected locations was 1.22, 1.43, and 1.33 Bq/m3 for Cs-137 and 0.88, 1.17, and 1.09 Bq/m3 for Sr-90 in surface seawater samples and 0.74, 1.01, and 0.81 Bq/kg dry for Cs-137 and 0.49, 0.49, and 0.43 Bq/kg dry for Sr-90 in sediment samples. The ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In terms of acceptability, HIVST kit usage in other studies were found to be usable across the key populations, particularly on MSM and TGW [4,38,39,45,46], which is similar to the findings from our study. In addition, reports on social harm were not observed during the implementation of our study, a result comparable in other studies [47][48][49], while other studies reported otherwise [50][51][52][53][54]. However, stigma still plays a role in HIV diagnosis in the Philippines, and self-harm could still be possible after receiving a diagnosis.…”
Section: Hivst Cascadesupporting
confidence: 81%
“…In terms of acceptability, HIVST kit usage in other studies were found to be usable across the key populations, particularly on MSM and TGW [4,38,39,45,46], which is similar to the findings from our study. In addition, reports on social harm were not observed during the implementation of our study, a result comparable in other studies [47][48][49], while other studies reported otherwise [50][51][52][53][54]. However, stigma still plays a role in HIV diagnosis in the Philippines, and self-harm could still be possible after receiving a diagnosis.…”
Section: Hivst Cascadesupporting
confidence: 81%
“…This means it is likely that the organic matter composition in the sediment from Dixcove could have affected the retention and migration of the 137 Cs radionuclide through the modification of the adsorption properties of the clay minerals in the sediment. Thus, due to this phenomenon 137 Cs gets trapped in sediment restricting its movement [ [32] , [33] , [34] , [35] , [36] ]. Again, high 137 Cs activity concentration is known to be influenced by fine-grain particles as the concentration increases with decreasing particle sizes [ 17 , 18 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microalgae can be introduced not only in the biofiltration system but also as a component to utilize inorganic N and P for their enhanced growth, and the resulting biomass can be valorized as feed for other aquatic organisms (Milhazes-Cunha and Otero, 2017). Li et al (2019) and Nguyen et al (2019b) reported that Chlorella vulgaris produced higher biomass with a significant decrease in total N, total P, BOD, and COD when recycled aquaculture wastewater was used as the culture medium. showed that microalgae produced higher biomass and nutritional contents when cultured in fishery wastes.…”
Section: Bioremediationmentioning
confidence: 99%